Studies on microflora in boiled milk - Mukundan M (Department of Dairy Science, College of Veterinary and Animal Sciences, 1978)
A study was carried out to determine the total spore count, the incidence and distribution of the different types of the aerobic spore – formers present in milk boiled for one minute. The keeping quality of raw as well as boiled milk stored at 370C, 290C and 40C was determined and compared. The samples of milk required for the study were collected from the University Livestock Farm, Mannuthy, Co – operative Milk Supply Union, Trichur and individual households around Trichur Town. A total of 48 samples of milk were collected. The spore count in the samples was determined after subjecting them to boiling for one minute. The spore count for the samples of milk collected from the ranged from 10 to 190 per ml whereas the range was 40 to 155 per ml and 10 to 150 per ml for those obtained from Co – operative Milk Supply Union and individual households respectively. The average spore count of the 48 samples studied was 69 per ml. A total of 162 isolates were identified as Bacillus subtilis 85, Bacillus cerus 23, Bacillus pumillus 20, Bacillus licheniformis 15, Bacillus megaterium 11, Bacillus alvei 6 and Bacillus firmis 2. The samples from all the sources revealed the predominance of Bacillus subtilis and it accounted for more than 52.5 per cent of the isolates. Out of the 48 samples of raw milk stored at 370 C, 34 had a keeping quality of less than eight hours and the remaining 8 and 12 hours. When raw milk was stored at room temperature (290 C) 20 had a keeping quality of less than eight hours, and it was 8 to 12 hours for 28 samples. At refrigeration temperature of 40 C, 41 samples remained good for five days and in the other seven samples the keeping quality was for six days. When the keeping quality of boiled milk stored at 370 C was studied, 4 out of 48 had a keeping quality of less than eight hours and the remaining 44 samples had 8 to 12 hours of keeping quality. At room temperature (290 C) the keeping quality was 8 to 12 hours for 38 samples as against the same of 12 to 16 hours and 16 to 20 hours for 8 and 2 samples respectively. When the samples of boiled milk were stored at refrigeration temperature (40 C), 19 out of 48 samples had a keeping quality of 13 days. The keeping quality was found to be 16 days for three of the samples stored at 40 C. Some of the procedures necessary to improve the keeping quality of boiled milk have been suggested.